2002
DOI: 10.1046/j.1365-8711.2002.05832.x
|View full text |Cite
|
Sign up to set email alerts
|

The classification of BL Lacertae objects: the Ca H&K break

Abstract: We investigate why BL Lacertae objects (BL Lacs) have values of the Ca H&K break (a stellar absorption feature) lower than low-power radio galaxies and if its use is justified to separate the two classes. For this purpose we relate this parameter to the radio and optical core emissions, as well as to the X-ray powers, for a sample of ~90 radio sources. We find that the Ca H&K break value decreases with increasing jet powers, and that it also anti-correlates with the radio core dominance parameter but not with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 56 publications
6
125
1
Order By: Relevance
“…We also estimated a lower limit for the jet-to-host ratio assuming that the host galaxy is a bright elliptical and found a jet-to-galaxy ratio > ∼ 20−40. For this high ratio, a featureless spectrum is expected (Landt et al 2002). Therefore, the observed spectrum of PKS 0447-439 is also consistent with the proposed redshift.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We also estimated a lower limit for the jet-to-host ratio assuming that the host galaxy is a bright elliptical and found a jet-to-galaxy ratio > ∼ 20−40. For this high ratio, a featureless spectrum is expected (Landt et al 2002). Therefore, the observed spectrum of PKS 0447-439 is also consistent with the proposed redshift.…”
Section: Discussionsupporting
confidence: 85%
“…In other words, the probability that the host galaxy of PKS 0447-439 is a member of the reported group is > ∼ 97%. Landt et al (2002) suggested that BL-Lac spectra become featureless for jet-to-galaxy luminosity ratios > ∼ 10. In the case of PKS 0447-439, where the spectrum was taken with a high signal-to-noise ratio, a jet-to-galaxy ratio > ∼ 20−40 might be more appropriate (compare the spectrum in Fig.…”
Section: Pks 0447-439 As a Group Membermentioning
confidence: 99%
“…Giommi et al 2012a). Following the work of Landt et al (2002) and Piranomonte et al (2007), we assume a giant elliptical host galaxy to be present in every blazar that would leave no imprint on the optical band if the total observed flux f obs exceeds the galaxy flux f ell by at least a factor of 10. Therefore, a lack of redshift allows us to set a lower limit based on the apparent magnitude m in the optical band.…”
Section: Lower Limits On Redshiftsmentioning
confidence: 99%
“…Historically, large and fast optical variability was one of the parameters used to define the BL Lac objects (see e.g., Landt et al 2002). There is more than one way to define a numerical index to quantify the variability of a source, like those used by Abdo et al (2010b).…”
Section: Nir and Optical Observationsmentioning
confidence: 99%